2008
DOI: 10.14494/jnrs.9.1
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics Study for the Sorption of <SUP>134</SUP>Cs and <SUP>60</SUP>Co Radionuclides from Aqueous Solutions

Abstract: The removal of cesium and cobalt radionuclides from aqueous chloride solutions using hydrous titanium oxide was investigated. The influence of initial ion concentration, pH, and temperature has been reported. The data obtained have been correlated with Langumir, Freundlich, and Dubinin-Radushkevich (D-R) isotherm models. The effect of temperature on the equilibrium distribution values has been investigated. The thermodynamic parameters such as free energy (∆G o ), enthalpy (∆H o ) and entropy (∆S o ) have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Venkataramani [7] has found that sorption of 137 Cs on hydrated titanium dioxide becomes noticeable at pH 4 and increases significantly upon transfer to alkaline medium-at pH 10 sorption is more than 10 times higher than at pH 4. Metwally [8] studied thermodynamic parameters of caesium ion sorption onto titanium dioxide. According to his data, upon the increase of temperature Gibbs free energy of the sorption process decreases, which makes this process more favorable from a thermodynamic point of view-reaction ability of titanium dioxide increases, and after the temperature rises from 25 to 50 • C, the amount of caesium sorped approximately increases twofold.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Venkataramani [7] has found that sorption of 137 Cs on hydrated titanium dioxide becomes noticeable at pH 4 and increases significantly upon transfer to alkaline medium-at pH 10 sorption is more than 10 times higher than at pH 4. Metwally [8] studied thermodynamic parameters of caesium ion sorption onto titanium dioxide. According to his data, upon the increase of temperature Gibbs free energy of the sorption process decreases, which makes this process more favorable from a thermodynamic point of view-reaction ability of titanium dioxide increases, and after the temperature rises from 25 to 50 • C, the amount of caesium sorped approximately increases twofold.…”
Section: Introductionmentioning
confidence: 99%
“…Bignon [1] only studied the composition of film and not its contamination with radionuclides. Some authors [6][7][8][9][10][11] studied sorption of cobalt and caesium radionuclides but either freshly precipitated hydrated titanium dioxide or nanocomposites from hydrated and non-hydrated titanium dioxide were used as sorbents. At the same time, freshly precipitated hydrated titanium dioxide has a large specific surface area (ca.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation